Keragaman Jenis Burung Air Di Kawasan Hutan Mangrove Primer Dan Hutan Mangrove Hasil Reboisasi Di Kabupaten Mempawah - Ari Hepi Yanti, Angga, Tri Rima Setyawati (Universitas Tanjungpura, 2015)
Waterbird is a key species (keytone species) that can be used as one of the decisive criteria for the condition of a wetland. This study aims to determine differences in the types and degree of diversity of waterbird in the area of ​​primary mangrove forests and reforestation mangrove. This study uses the encounter rate method (meeting level). Waterbird that found are documented and identified directly in the field. Observations at both locations was found 17 species of waterbird are included in 5 families (Alcedinidae, Ardeidae, Rallidae, Scolopacidae and Sternidae). Waterbird from Sternidae family are the most found waterbird. Diversity index of waterbird species in primary mangrove forest Desa Peniti Kecil H'= 2.1388 is higher than reforestation mangrove Desa Sungai Bakau Kecil H' = 1.8692, both of them included in the medium category. Based on the results of the calculation of the t-test (2.9713> 1.97) both sites have a significantly different level of diversity. Dominance index and evenness index were obtained in primary mangrove forest Desa Peniti Kecil is D = 0.1360, E = 0.8338 and reforestation mangrove is D = 0.2160, E = 0.7522 indicates both locations observations no waterbird which extremely dominates and the number of individuals in observation locations almost spread evenly.